Lumican is upregulated in osteoarthritis and contributes to TLR4-induced pro-inflammatory activation of cartilage degradation and macrophage polarization. Issue 1 (January 2020) - Barreto, G.; Senturk, B.; Colombo, L.; Brück, O.; Neidenbach, P.; Salzmann, G.; Zenobi-Wong, M.; Rottmar, M.
Summary: Objective: Lumican (LUM) is a major extracellular matrix glycoprotein in adult articular cartilage and its expression is known to be upregulated upon cartilage degeneration. LUM is associated with the pathogen-associated molecular pattern (PAMP) activation of the TLR4 signalling cascade, with TLR4 being highly associated with inflammation in rheumatic diseases. However, the main role of the LUM structural molecule in osteoarthritis (OA) remains elusive. The aim of this study was, therefore, to understand the role of LUM during TLR4-mediated activation in OA. Methods: After measuring LUM levels in synovial fluid (SF) of OA patients and lipopolysaccharide (LPS)-induced TLR4 activation, the role of LUM in the expression of pro-inflammatory molecules and cartilage degradation was assessed in vitro and ex vivo in a cartilage explant model. Primary macrophage activation and polarization were studied upon LUM co-stimulation with LPS. Results: We demonstrate that LUM is not only significantly upregulated in SF from OA patients compared to healthy controls, but also that LUM increases lipopolysaccharide (LPS)-induced TLR4 activation. Furthermore, we show that a pathophysiological level of LUM augments the LPS-induced TLR4 activation and expression of downstream pro-inflammatory molecules, resulting in extensive cartilage degradation. LUM co-stimulation with LPS also provided a pro-inflammatory stimulus, upregulating primary macrophage activation and polarization towards the M1-like phenotype. Conclusions: These findings strongly support the role of LUM as a mediator of PAMP-induced TLR4 activation of inflammation, cartilage degradation, and macrophage polarization in the OA joint and potentially other rheumatic diseases.